MONITORING A CONDITION OF RECOVERY OF RESIDUAL STAND AND LOGGED OVER AREA AFTER 5 YEARS RIL IMPLEMENTATION: A CASE STUDY AT A FOREST COMPANY IN CENTRAL KALIMANTAN - Sukanda Sukanda; Yuniawati Yuniawati; Sona Suhartana (Indonesian Journal of Forestry Research, 2007)
The aim of this study were to identify and evaluate a condition in logged over area (LOA) after 5 years of reduced impact logging (RIL) implementation, and to asses how far recovery of former skidding road, damages in felled and yarded over area, and environmental condition had taken place. Results of this study was expected to provide inputs and to improve the RIL implementation guidance for sending   sustainable forest management. The results revealed that: (1)The covers of skidding road reached consecutively 2,641 m2  area (in block I), and 3,147 m2  area (in block II), as both marked by the growing of  bushes with coverage portions i.e. 84% and 80%, respectively; (2) The bush that grew on the former skidding road was regarded as pioneer vegetation; (3) The effect of cross drain on skidding road after logging was able to decrease erosion, and increase the recovery of the road condition; and (4) The healthy residual stand after 5 years logging by RIL showed that small diameter felled trees have resulted bigger residual stand damaged then big diameter or the percentage of healthy trees would be small.